2010
DOI: 10.1021/ja1028843
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule-Capped Gold Nanoparticles as Potent Antibacterial Agents That Target Gram-Negative Bacteria

Abstract: This report illustrates a new strategy in designing antibacterial agents--a series of commercially available compounds, amino-substituted pyrimidines (themselves completely inactive as antibiotics), when presented on gold nanoparticles (NPs), show antibacterial activities against multidrug-resistant clinical isolates, without external sources of energy such as IR. These pyrimidine-capped gold NPs exert their antibiotic actions via sequestration of magnesium or calcium ions to disrupt the bacterial cell membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
440
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 551 publications
(454 citation statements)
references
References 57 publications
14
440
0
Order By: Relevance
“…Despite considerable recent progress in the understanding of the mechanisms underlying bacterial infections, and in the development of nanostructured materials displaying antibacterial properties and activity against biofilms [1], [5], [6], [7] and [8], the quest to design and fabricate new antibacterial nanostructures remains a high research priority. Nanoparticles have been considered as affective solution to fight against bacterial infections [4], [9], [10], [11], [12], [13], [14] and [15]. Such nanostructures allow the concentration of antibacterial agents and functions on their surface to deliver polyvalent effects.…”
Section: Introductionmentioning
confidence: 99%
“…Despite considerable recent progress in the understanding of the mechanisms underlying bacterial infections, and in the development of nanostructured materials displaying antibacterial properties and activity against biofilms [1], [5], [6], [7] and [8], the quest to design and fabricate new antibacterial nanostructures remains a high research priority. Nanoparticles have been considered as affective solution to fight against bacterial infections [4], [9], [10], [11], [12], [13], [14] and [15]. Such nanostructures allow the concentration of antibacterial agents and functions on their surface to deliver polyvalent effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, silica covering could provide large specific surface area for more TMB loading by the interaction with protein molecules present in the bacteria. 28,38 But, Gao et al presented an interesting report for the high TMB signals. 41 Increase in enzyme concentration or H 2 O 2 with TMB substrate creates multiple nucleation centers to form different self-assembled nanostructures by producing different colors due to charge-transfer complex.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Gold nanostructures have recently been useful in bio-applic ations because of their nontoxicity, ease of surface modification, polyvalent effects, and photothermal capacity. [25][26][27] Zhao et al 28 and Ma et al 29 developed organic molecule-attached gold nanoparticles for bacteria lyses through cell membrane rupture, attachment with nucleic acids, and inhibition of protein synthesis. There are no existing reports that explain the interaction of metal nanostructures with E. coli O157 and its enzymatic activity without H 2 O 2 .…”
Section: Ramasamy Et Almentioning
confidence: 99%
“…In a recent study, authors reported that negatively charged GNP cannot inhibit Pseudomonas aeruginosa compared to the positively charged GNP, 37 while the bacterial activity of positively charged GNP was higher than the negatively charged counterparts in another study. 38 Our results indicated that the MIC value of the anionic PAA-GNR is not significantly different than that for neutral PEG-GNR, and the MIC value of PAA-GNR 2 is not significantly different than that for cationic PEG-Cys-GNR or neutral PEG-GNR 2 against S. aureus and P. acnes.…”
Section: 28mentioning
confidence: 94%